2012
DOI: 10.1002/ece3.100
|View full text |Cite
|
Sign up to set email alerts
|

Integrating species distribution models (SDMs) and phylogeography for two species of Alpine Primula

Abstract: The major intention of the present study was to investigate whether an approach combining the use of niche-based palaeodistribution modeling and phylo-geography would support or modify hypotheses about the Quaternary distributional history derived from phylogeographic methods alone. Our study system comprised two closely related species of Alpine Primula. We used species distribution models based on the extant distribution of the species and last glacial maximum (LGM) climate models to predict the distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 86 publications
2
49
0
1
Order By: Relevance
“…In the south western Alps, survival in peripheral refuges and nunataks during the LGM has recently been demonstrated in Primula spp. using both SDM and phylogeographical approaches [12]; however, our results are congruent with previous findings in the Maritime and Ligurian Alps where glaciations seem to have had a low influence on plant distribution and their effect seems to be weakened by high level of postglacial migrations [81]. These findings are more similar to that expected for a Mediterranean mountain region [7, 8] rather than for an Alpine region [16, 58], where patterns were simplified to a great extent by major losses of diversity during glacial periods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the south western Alps, survival in peripheral refuges and nunataks during the LGM has recently been demonstrated in Primula spp. using both SDM and phylogeographical approaches [12]; however, our results are congruent with previous findings in the Maritime and Ligurian Alps where glaciations seem to have had a low influence on plant distribution and their effect seems to be weakened by high level of postglacial migrations [81]. These findings are more similar to that expected for a Mediterranean mountain region [7, 8] rather than for an Alpine region [16, 58], where patterns were simplified to a great extent by major losses of diversity during glacial periods.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed understanding of the effects of past climate changes on the distribution and genetic pattern of organisms may help us to better predict the effects of ongoing climate change [9, 10]. It has been recently demonstrated that the combination of paleo-distribution modelling with phylogeographical approaches may led to new interpretations of population genetic patterns and to new hypotheses about glacial survival and postglacial colonization [11, 12, 13]. …”
Section: Introductionmentioning
confidence: 99%
“…The LGM climate over Europe as simulated by CCSM is colder and drier than that of MIROC (Schorr et al. 2012) and allowed us to evaluate modeling performance with two sets of climate data. For the LIG data model projection, we used the only data set available (Otto‐Bliesner et al.…”
Section: Methodsmentioning
confidence: 99%
“…Th e strong range expansion of T. g. graeca since the LGM predicted the ENMs was clearly supported both by neutrality tests ( F S, Tajima ' D and R 2 ), a unimodal mismatch distribution and coalescent-based analyses (EBSP). Alternatively, given the complexity of biogeographical histories, several ad hoc hypotheses could explain these apparently incongruent patterns (Schorr et al 2012). However, the strong range contraction predicted in T. g. marokkensis did not match the population increase described by non-genealogical summary statistics, and neither the results from EBSP analysis, which depicted a slight growth but did not allow rejecting population stability.…”
Section: Response To Past Climate Changesmentioning
confidence: 99%